Kebebasan berbicara versus pertimbangan keamanan cyber menurut perspektif hukum dan HAM : FREEDOM OF SPEECH VERSUS CYBER SECURITY CONSIDERATIONS: FROM A LEGAL AND HUMAN RIGHTS PERSPECTIVE - Nurhayati, Siti; Salsabila , Lia; Hidayat, Rizal; Salsabila, Lia (Fakultas Hukum Universitas Trisakti, 2023)
Freedom of speech is a human right and is also stated in the 1945 Constitution of the Republic of Indonesia Article 28 E Paragraph 3 concerning freedom of association, freedom to express opinions or be given freedom of speech, but this freedom also has other provisions regarding the use of this right. in the regulations regarding cyber security in Republic of Indonesia Law Number 3 of 2002 concerning Defense. The state states that national defense aims to maintain and protect the sovereignty of the country, the territorial integrity of the Unitary State of the Republic of Indonesia (NKRI) and the safety of the entire nation from all forms of threats, both military and non-military threats. Non-military threats, especially in cyber space, have caused the country's capabilities in the field of soft and smart power defense to be improved through strategies for deterring, taking action and restoring cyber defense in order to support the implementation of the national cyber security strategy driven by the Ministry of Communication and Information. Indonesian law also does not provide legal certainty in dealing with cyber attacks such as cyber espionage. Cyber security is not only the responsibility of the government, but also the responsibility of every individual. Awareness about the dangers of cyber espionage needs to be instilled in everyone. The National Police has a role in protecting society from cyber attacks.